Diagnosis of Coronary Artery Fistulas: Clinical Aspects and Brief Review of the Literature - Sharma, Umesh M.; Aslam, Ahmed F.; Tak, Tahir (International Journal of Angiology, 2013)
An 86-year-old woman with history of hypertension, diabetes, hyperlipidemia, and coronary artery disease was admitted with new-onset congestive heart failure and pneumonia. She underwent coronary angiography after suffering a non-ST elevation myocardial infarction. There was severe coronary artery disease in addition to coronary artery–pulmonary fistulas involving proximal right coronary artery and a branch of left main coronary artery.Coronary artery fistula (CAF) is an abnormal communication between one or more coronary arteries and great vessels or a cardiac chamber. We reviewed 15 cases of CAFs published in PubMed and studied the clinical features of CAFs.
Keywords: congestive heart failure; fistulas; cardiac catheterization; angiography; coronary arteries